UNIVERSITY AUTONOMY: DEMOCRACY AGAINST TOTALITARISM - Mykhailo Boichenko; Nataliia Boichenko (Неперервна професійна освіта: теорія та практика)
The article analyzes the value, functional, and institutional advantages of developing university autonomy in a democratic society compared to comparable opportunities in a totalitarian society. The strengths and weaknesses of democratic and totalitarian governance as an institutional basis for establishing university autonomy are analyzed. The methodology of value functionalism by M. Boichenko and the counterfactual approach to academic values by N. Boichenko were used. The method of presenting the material is built on the classical principle of consistent formulation of the thesis, analysis of arguments that deny it, and the presentation of counterarguments that nevertheless confirm the initial thesis (following the example of the works of Thomas Aquinas). The fundamental value of academic freedom for the establishment of university autonomy and the fundamental error and harmfulness of M. Heidegger’s concept of serving the state and the fate of the nation as the basis for the university are revealed. Thus, the main flaw of the totalitarian method of establishing the “self-affirmation” of the university is revealed. The arguments against considering the commercialization of university education as detrimental to the development of the academic sphere in general and to the institutional functioning of universities in particular are clarified. The danger of the commercialization of universities is considered as a weak side of the democratic arrangement of university autonomy, which, however, can be largely neutralized through proper educational management and academic strategic planning. The command style of collective leadership under totalitarianism is contrasted with collegial decision-making under deliberative democracy. The particularism in the management style of totalitarian regimes is contrasted with the universalism of academic values as the basis for democratic university management.